A Comprehensive Review of the Diversity of Fungal Secondary Metabolites and Their Emerging Applications in Healthcare and Environment - Khushbu Wadhwa; Neha Kapoor; Hardeep Kaur; Eman A. Abu-Seer; Mohd. Tariq; Sazada Siddiqui; Virendra Kumar Yadav; Parwiz Niazi; Pankaj Kumar; Saad Alghamdi (Mycobiology)
Fungi and their natural products, like secondary metabolites, have gained a huge demand in the last decade due to their increasing applications in healthcare, environmental cleanup, and biotechnology-based industries. The fungi produce these secondary metabolites (SMs) during the different phases of their growth, which are categorized into terpenoids, alkaloids, polyketides, and non-ribosomal peptides. These SMs exhibit significant biological activity, which contributes to the formulation of novel pharmaceuticals, biopesticides, and environmental bioremediation agents. Nowadays, these fungal-derived SMs are widely used in food and beverages, for fermentation, preservatives, protein sources, and in dairy industries. In healthcare, it is being used as an antimicrobial, anticancer, anti-inflammatory, and immunosuppressive drug. The usage of modern tools of biotechnology can achieve an increase in demand for these SMs and large-scale production. The present review comprehensively analyses the diversity of fungal SMs along with their emerging applications in healthcare, agriculture, environmental sustainability, and nutraceuticals. Here, the authors have reviewed the recent advancements in genetic engineering, metabolic pathway manipulation, and synthetic biology to improve the production and yield of these SMs. Advancement in fermentation techniques, bioprocessing, and co-cultivation approaches for large-scale production of SMs. Investigators further highlighted the importance of omics technologies in understanding the regulation and biosynthesis of SMs, which offers an understanding of novel applications in drug discovery and sustainable agriculture. Finally, the authors have addressed the potential for genetic manipulation and biotechnological innovations for further exploitation of fungal SMs for commercial and environmental benefits.